Development of Processed Products Made from Sweet Potatoes into Sweet Potato Milk (Violatte) to Improve the Economy of the Community in Dopang Village, West Lombok Regency - Ahmad Harjono; Ahmad Busyairi; Hairunisa Sahidu; Itsna Hasanah; Sir Atinnur Rahman; Chintya Ananditha; Nurhasanah Nurhasanah; Nurjannah Nurjannah; Ari Nashiruddin Zaini; Mardiyanti Mardiyanti; Astuti Astuti; Siti Hajar; Sulastri Sulastri; Herlinda Febriani; Ni Putu Puspa Widyarni Sari (Unram Journal of Community Service, 2022)
The potential of sweet potatoes in Dopang Village, West Lombok Regency is quite abundant, especially the type of purple sweet potato. In addition to its good health benefits, the existence of purple sweet potato also has high economic potential. Processing of purple sweet potatoes into more valuable products in Dopang Village is still considered lacking. Based on observations, the processing of purple sweet potatoes in the surrounding community is only in the form of snacks or chips. Therefore, this activity aims to develop processed products made from purple sweet potatoes into products in the form of sweet potato milk (Violatte) in the hope of increasing the economy of the local community. This activity is carried out in 4 (four) stages, namely; (1) product manufacturing experiment, (2) product improvement, (3) product socialization to the public, and (4) product marketing. The activity is carried out for approximately 1.5 months from November 22, 2021 - January 6, 2022. The location of the activity is in Dopang Tengah Hamlet, Dopang Village, Gunungsari, West Lombok, West Nusa Tenggara (NTB). Each stage of this activity, starting from product manufacturing trials, product improvement stages, socialization stages and product marketing stages has been carried out and is running well.